Experimental vs. modeled water use in mature Norway spruce (Picea abies) exposed to elevated CO2 - Leuzinger, Sebastian; Bader, Martin (Frontiers in Plant Science, 2012)
Rising levels of atmospheric CO2 have often been reported to reduce plant water use. Such behaviour is also predicted by standard equations relating photosynthesis, stomatal conductance, and atmospheric CO2 concentration, which form the core of global dynamic vegetation models (DGVMs). Here, we provide first results from a free air CO2 enrichment (FACE) experiment with naturally growing, mature (35 m) Picea abies (L.) (Norway spruce) and compare them to simulations by the DGVM LPJ-GUESS. We monitored sap flow, stem water deficit, stomatal conductance, leaf water potential and soil moisture in five 35-40 m tall CO2-treated (550 ppm) trees over two seasons. Using LPJ-GUESS, we simulated this experiment using climate data from a nearby weather station. While the model predicted a stable reduction of transpiration of between 9 and 18 % (at concentrations of 550-700ppm atmospheric CO2), the combined evidence from various methods characterising water use in our experimental trees suggest no changes in response to future CO2 concentrations. The discrepancy between the modelled and the experimental results may be a scaling issue: while dynamic vegetation models correctly predict leaf-level responses, they may not sufficiently account for the processes involved at the canopy and ecosystem scale, which could mitigate the first-order stomatal response.